JWST confirms that quasars do not evolve across cosmic time - Bosman, Sarah (Nature astronomy, 2024)
Although stars and galaxies have developed over time, it seems that supermassive black holes already existed at the ‘cosmic dawn’ of the Universe. Analysis of the mid-infrared spectrum of an early quasar (a quasi-stellar object powered by a black hole) suggests that supermassive black holes and their feeding mechanisms were already completely mature when the Universe was 5% of its present age.
Online verfügbar: 17. Juni 2024
Gesehen am 14.11.2024